Correlation and repeatability in progenies of African oil palm = Correlações e repetibilidade em progênies de dendê - Digner Santiago Ortega Cedillo; Willian Silva Barros; Fábio Medeiros Ferreira; Luiz Antônio dos Santos Dias; Rodrigo Barros Rocha; Cosme Damião Cruz (Acta Scientiarum: Agronomy, 2008)
The phenotypic, genotypic and environmental correlations between thenumber of palm fruit bunches and the annual yield and their combinations in African palm were estimated. There were also estimated the coefficients of repeatability and determination, with the objective of indicating the lowest number of successive harvestsrequired to exploit the genotypic potential of the evaluated progenies. The genotypic correlation between the number of bunches per plant and the yield was negative, indicating that when genotypes with a higher yield are selected the number of bunches decreases. Ingeneral, the signal of the genotypic correlation differed was opposite to the one from the environmental correlation, evidencing that genetic and environmental factors influence the number of bunches and yield through different physiological mechanisms. Based on the method of principal components applied to the correlation matrix, at least four years of evaluation seem to be necessary, values coefficients of reliability and repeatability were87.6% e 0.64, respectively. Estimaram-se as correlações fenotípicas, genotípicas e ambientais entre o número de cachos por planta e a produção anual e suas combinações em dendê (Elaeis guineensis). Os coeficientes derepetibilidade e de determinação também foram estimados, com o objetivo de indicar o período mínimo de colheita necessário para se acessar o potencial genotípico das progênies avaliadas. A correlação genotípica entre o número de cachos e a produção foi negativa,indicando que, se forem selecionados os genótipos com maior produção, o número de cachos deverá diminuir. A correlação genotípica geralmente apresentou sinal oposto do que precedia correlação ambiental, evidenciando que as causas genéticas e ambientaisinfluenciam o número de cachos e a produção por meio de mecanismos fisiológicos distintos. Com base no método de componentes principais aplicado à matriz de correlação, o período mínimo de colheitas foi de quatro anos, com confiabilidade de 87,6% e coeficiente de repetibilidade de 0,64.